Diseño y construcción de una máquina para el proceso de siembra en pendientes para el cultivo de maíz - Manrique Fernández, Alvaro Damián (2023)
The design project of a mechanical corn seed planter aims to provide a cost-effective and efficient solution for farmers working on sloping terrains. The created machine is innovative and easy to operate and features a good seed storage capacity and low maintenance cost, which reduces the need for additional labor. Furthermore, after conducting the design and simulation process for the planter, satisfactory results have been obtained in terms of strength and efficiency. Firstly, it has been determined that the diameter of the seed storage hopper should be 44 mm and its length 1.2 m to ensure continuous seed feeding. Additionally, it has been calculated that the length of the crank should be 2.5 cm to allow for the rotation of the seed selection mechanism and constant seed discharge. Regarding the crucial component of the driving mechanism, the spring, being made with a steel alloy (18CrMoS4), simulation results show that it has adequate strength of 5418,33 psi, allowing it to withstand a force of 12 lbf without damage, as it produces a shear stress of 40420 psi, and has a safety factor of 3.5.